Interaction between PPARA genotype and ββ-blocker treatment influences clinical outcomes following acute coronary syndromes. (October 2008) - Cresci, Sharon; Jones, Philip G; Sucharov, Carmen C; Marsh, Sharon; Lanfear, David E; Garsa, Adam; Courtois, Michael; Weinheimer, Carla J; Wu, Jun; Province, Michael A; Kelly, Daniel P; McLeod, Howard L; et al.
Aims: ββ-blockers (BB) are strongly recommended after an acute coronary syndrome (ACS), although all patients may not benefit. Causes for variable patient responses to BB are unknown. Given that myocardial ischemia and BB influence metabolic processes regulated by peroxisome proliferator-activated receptor αα (PPARαα), we hypothesized that interactions between polymorphisms of the PPAR αα gene ( PPARA ) and BB treatment would influence clinical outcome following ACS.Patients & methods: Patients were prospectively enrolled into an ACS registry. A total of 735 ACS patients were genotyped. Mortality and cardiac rehospitalization through 1 year were analyzed in relation to PPARA genotype and BB prescription (597 BB; 138 no BB) at discharge.Results: Significantly different outcomes associated with BB therapy were observed according to PPARA IVS7 2498 genotype (p = 0.002 for interaction). PPARA IVS7 2498 GG homozygous patients discharged on BB had decreased cardiac rehospitalization (hazard ratio [HR]: 0.52; 95% CI: 0.32––0.86; p = 0.011), while C allele carriers discharged on BB had nearly threefold increased cardiac rehospitalization (HR: 2.92; 95% CI: 1.32––6.92; p = 0.015; genotype interaction p = 0.0005) compared with patients not on BB. PPARA genotype was also associated with differences in PPARαα expression, with significantly increased mRNA levels in myocardial samples from normal hearts among GC heterozygotes compared with GG homozygotes (p = 0.04). Transgenic mice with cardiac-specific overexpression of PPARαα showed significantly reduced myocardial contractile and chronotropic responses to the ββ-sympathomimetic dobutamine (p < 0.05) compared with wild-type littermates, supporting the hypothesis that increased PPARαα levels result in a blunted ββ-adrenergic response.Conclusions: PPARA IVS7 2498 genotype is associated with heterogeneity in 1-year outcome in response to BB among patients following ACS, and may predict which patients benefit from BB therapy, putatively related to the effect of myocardial PPARαα expression on ββ-adrenergic responsiveness.